2011
DOI: 10.1111/j.1445-5994.2010.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

POEMS (polyneuropathy, organomegaly, endocrinopathy, M‐protein and skin changes) syndrome in China

Abstract: POEMS syndrome in China has its own distinctive features, parts of which are commoner in the young people, the higher frequency of splenomegaly, hypothyroidism, hydropericardium and abnormal electrocardiogram, as well as the lower M-protein and bone lesions in X-ray.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Among our patients, the splenomegaly was the most common symptom (84.6%), which mirrors to the report of Cui et al [10]. Nevertheless, Li et al [18] reviewed the clinical characteristics of 99 Chinese POEMS patients and found 74 patients with lymphadenopathy, 70 with splenomegaly, and 47 with hepatomegaly.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Among our patients, the splenomegaly was the most common symptom (84.6%), which mirrors to the report of Cui et al [10]. Nevertheless, Li et al [18] reviewed the clinical characteristics of 99 Chinese POEMS patients and found 74 patients with lymphadenopathy, 70 with splenomegaly, and 47 with hepatomegaly.…”
Section: Discussionsupporting
confidence: 86%
“…It is a multisystem disorder associated with polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes [10, 11]. Elevation of proangiogenic and pro-inflammatory cytokines are the hallmark in the pathogenesis of this disorder [1215].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone lesions are hallmarks of POEMS syndrome and occurred in 95% of cases in a cohort in the United States (11) and 27%-46% in Chinese cohorts (11,(13)(14)(15). In our study, 74.7% of the patients had bone lesions, which contributed to detection of a greater number of tiny skeletal abnormalities on CT, compared with the traditional radiographic skeletal survey-43.3% of all the patients had 18 F-FDG-avid bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Another feature that aids the differential diagnosis is multiple cavity effusion without metabolism distribution, especially when the percutaneous area is involved simultaneously, which is a rare manifestation in other systemic diseases. The ascitic fluid may be exudative, but the detailed mechanism is still unclear (13).…”
mentioning
confidence: 99%